Eras u belaruskaj tradycyjnaj kul’turyEros v beloruski ljudski kulturi - Lobač, Uladzimir (Studia mythologica Slavica, 2015)
The article is dedicated to sexual symbolism and relations in the Belarusian traditional culture of the 19th - early 20th centuries. Analyzing a great number of ethnographical and folkloristic sources, the author investigates peculiarities of the sexual culture and symbolism in the Belarusian ethnic community of the 19th - early 20th centuries. Special attention is paid to erotic components in the youth subculture of the Belarusians; sexual motivations in wedding and birth rites as well as everyday life stereotypes of sexual relations are characterized.